Comparison of Hemorrhagic Risk in Intracranial Arteriovenous Malformations Between Conservative Management and Embolization as the Single Treatment Modality. Issue 4 (5th May 2017) - Yang, Wuyang; Porras, Jose L; Xu, Risheng; Braileanu, Maria; Khalid, Syed; Hung, Alice L; Caplan, Justin M; Garzon-Muvdi, Tomas; Rong, Xiaoming; Colby, Geoffrey P; Coon, Alexander L; Tamargo, Rafael J; et al.
Abstract: BACKGROUND: Embolization has been discussed as a feasible single modality treatment for intracranial arteriovenous malformations (AVMs). OBJECTIVE: To compare hemorrhagic risk between embolization and conservative management in a multivariate survival analysis. METHODS: We retrospectively reviewed records of patients with intracranial AVMs evaluated at our institution from 1990 to 2013. We included patients recommended to undergo embolization without other treatment modalities and patients managed conservatively. Multivariate Cox regression analysis of hemorrhage-free survival was performed, with the survival interval right-censored to date of either last follow-up or salvage treatment. RESULTS: We identified 205 patients matching our inclusion criteria, with 160 patients in the noninterventional group and 45 in the embolization group. The average age of all patients was 40.2 ± 19.5 yr, with younger patients undergoing embolization more often ( P = .026). Fifty-one (31.9%) conservatively managed patients and 13 (28.9%) patients treated by embolization ( P = .703) presented with hemorrhage. Other baseline characteristics were similar between the 2 management groups. During an average follow-up period of 7.7 yr, 30 patients (14.6%) experienced hemorrhage recurrence. Multivariate Cox regression revealed older age ( P = .031) and hemorrhagic presentation ( P < .001) to be statistically associated with follow-up hemorrhage. In a subset analysis of unruptured AVMs, embolization was associated with a 4-fold hazard ratio of hemorrhage compared to conservative management ( P = .044). CONCLUSION: Older age and initial presentation with hemorrhage were associated with increased risk of hemorrhage during follow-up. Treatment of AVMs with embolization as the sole modality may increase hemorrhagic risk compared with conservative management, especially in unruptured AVMs.